Манипулятивная составляющая социального взаимодействия в контексте политического маркетинга - Купцов, А. (Социология: теория, методы, маркетинг, 2004)
The article is devoted to analysis of manipulation aspects of social interaction within
political marketing context. The author considers the concept of manipulation, shows
the specific of sociological approach in this field. The main problem is the relation of
manipulation in electoral process in Ukraine with the democratic changes of the Ukrainian political culture during the last decade. Special attention is paid to con
sideration of the mass media role, problems of Ukrainian information space, potentials
of manipulation component within election campaigns. The main conclusion is that the
usage of manipulative technologies makes possibilities of political marketing more
sizable, but influences perspectives of democracy in Ukraine. The author's view may
be interesting for scholars in the field of politics, mass communications and social
psychology.